GENDER DIFFERENCES IN THE USE OF PARTS OF SPEECH: AN ANALYSIS OF POPULAR AND FEMINA MAGAZINES - MEODIA, ARINDRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This research focuses on analyzing the differences of male andfemale magazines in the use of parts of speech which arepronouns and specifiers. Popular and Femina magazines areselected as the data sources since the contents of Popular arebelieved to represent male’s characteristics and of Femina arebelieved to represent female’s characteristics. Furthermore, theresearcher takes six steps in analyzing the data: identifying,organizing and coding the data, displaying the data intonumbers, analyzing the data found, discussing the finding, anddrawing conclusion. The results show that there are eight topicsout of thirteen topics in which pronouns are used with greaterfrequency in Femina rather than in Popular. Femina usespronouns in higher percentage rather than Popular. Thepercentage is 44.6% for Femina and 37.3% for Popular.Therefore, it can be inferred that pronouns are used with greaterfrequency in female magazine (Femina) rather than malemagazine (Popular).Keywords: Gender, Gender Differences, Pronouns, Specifiers,Magazine